Crypto Digital Asset Phenomenon in Hadith Review with Anthro-Economic Social Approach - Apriliah Apriliah; Wahyudin Darmalaksana (Khazanah Hukum, 2022)
This study aims to discuss the phenomenon of crypto digital assets in the review of hadith through an anthropo-economic social approach. This study uses a qualitative approach through descriptive-analytical methods. The results of the research and discussion show that cryptocurrency can be understood as a digital currency for virtual transactions or those based on an internet network in which there are differences of opinion among scholars. This study concludes that the use of crypto is prohibited based on the hadith about buying and selling that can lead to gharar and according to the views of scholars in Indonesia, this is related to the precautionary principle as far as cryptocurrency has not guaranteed security in the implementation of the socio-anthro-economic perspective of the Islamic community. This study recommends Islamic economic institutions such as Islamic financial services authorities and Islamic banking to conduct a more in-depth study of security guarantees in the use of digital crypto in Indonesia.